Characterization of Processing Influences on In Vitro Bioaccessibility of Carotenoids and Chlorophylls from Six Spinach Genotypes. (29th May 2020) - Hayes, Micaela; Pottorff, Marti; Kay, Colin; Lila, Mary Ann; Iorizzo, Massimo; Ferruzzi, Mario
Abstract: Objectives: Spinach is a rich source of bioactives including carotenoids and chlorophylls. Ultimate delivery, or bioavailability, of these bioactives to consumers varies depending on pre-/post-harvest factors that impact the food matrix. The interaction between food processing, oral processing (mastication), and spinach genotype have not been explored. Insights into these factors hold the potential to identify interaction effects between genotype and processing (GxP). Methods: Six genotypes of spinach selected based on previous bioaccessibility screening were greenhouse grown in Salisbury, NC (Fall 2019), harvested, and stored fresh at 4C (24 hr) or at −80C after processing by blanching (2 min, 100C), thermal sterilization (121C for 15 min), or juicing. All genotypes were subjected to all processing methods, and a portion of each sample was subjected to simulated mastication while another was homogenized (30 sec) into a puree. All samples were subjected to a three-phase in vitro digestion to assess the transfer of carotenoids and chlorophyll derivatives from the food matrix to the aqueous micellar fraction (bioaccessibility). Results: Processing method, genotype, and GxP had a significant influence on total bioactive content ( P < 0.01), relative bioaccessibility ( P < 0.01), and bioaccessible content ( P < 0.01). Average bioactive content decreased in the order of juiced (26.2–36.9 μmol/g), blanched (23.3–30.0 μmol/g), thermally sterilized (22.5–27.3 μmol/g), and fresh spinach (18.6–25.0 μmol/g). Bioaccessible content decreased from juiced (6.8–9.8 μmol/g), to fresh (4.0–6.9 μmol/g) and blanched (4.6–5.6 μmol/g), and then thermally sterilized (2.4–3.3 μmol/g). Bioaccessible content from masticated samples was similar for thermally sterilized (0.9–1.5 μmol/g) and fresh samples (0.7–1.3 μmol/g). Conclusions: Results indicate that heat treatment preserves bioactives in these six spinach genotypes and may modestly decrease their bioaccessibility. Influence of mastication on bioaccessible content of bioactives supports the notion that oral processing is a critical factor impacting ultimate bioaccessibility from vegetables. Together, these results provide valuable information for optimization of bioactive delivery. Funding Sources: Foundation for Food and Agriculture Research.